Does Bone Regrow After Notchplasty in ACL Reconstruction? A Prospective Computed Tomography Study With 2-Year Follow-up. Issue 9 (6th September 2021) - Kitridis, Dimitrios; Tsifountoudis, Ioannis; Georgiannos, Dimitrios; Tsikopoulos, Konstantinos; Givissis, Panagiotis; Bisbinas, Ilias
Background: During notchplasty in anterior cruciate ligament (ACL) reconstruction, bone is excised from the lateral and roof area of the notch to widen the intercondylar space and avoid notch-graft impingement in extension. There are concerns that bone regrowth of the area will cause narrowing and increase the risk of complications. Purpose: To determine the possibility of late narrowing of the notch after notchplasty using computed tomography (CT) analysis. Study Design: Case series; Level of evidence, 4. Methods: Measurements were performed on CT scans (axial and sagittal planes with knee in extension) in patients who had undergone single-bundle anatomic ACL reconstruction using hamstring graft. Two axial image levels were used: at the anterior outlet and the anterior one-eighth level of the notch. The maximum notch height and width, the notch width at one-third and two-thirds of the preoperative notch midwidth height, the maximum condylar width, and the surface area of the lateral half of the notch were measured preoperatively and at 1 week and 2 years postoperatively. Results: Included were 20 consecutive patients (mean ± standard deviation age, 28 ± 7.3 years; follow-up, 24.2 ± 3.3 months). At the anterior notch outlet, the maximum notch width increased by 1.9 ± 1.7 mm at 1 week postoperatively and narrowed by 0.3 ± 1.1 mm at the final follow-up, while the maximum notch height increased by 1.7 ± 1.9 mm and narrowed by 0.8 ± 1.8 mm, respectively. At one-eighth of the roof length, the maximum notch width increased by 1.1 ± 1.7 mm at 1 week postoperatively and narrowed by 0.1 ± 1.1 mm at the final follow-up, and the maximum notch height increased by 1.2 ± 1.5 mm and narrowed by 0.5 ± 1.5 mm, respectively. All differences were statistically significant when comparing the pre- to the immediate postoperative measurements, and they were nonsignificant when comparing the immediate postoperative to the final follow-up measurements. The same applied for the ratio of maximum notch width to maximum condylar width, indicating no postoperative narrowing of the notch. Conclusion: Notch size-shape after a 2-mm notchplasty did not change significantly in stable knees during the first 2 years after anatomic ACL reconstruction. Surgeons should consider performing this adjuvant technique when there is notch-graft impingement during surgery.